Employee Performance: The Role of Workload and Job Insecurity (An Empirical Study at PT STL Indonesia.) - Mewaini, Tantri; Santati, Parama; Cahyadi, Afriyadi (GREENOMIKA, 2025)
Workload and job insecurity are important factors that need to be managed effectively, as both can impact employee performance. This study aims to determine and analyze the influence of workload and job insecurity on the performance of employees in the Production Department at PT STL Indonesia (STL). This study used a quantitative descriptive method. The sampling technique used incidental sampling, with 72 respondents from the Production Department at PT STL Indonesia (STL). Data were obtained through questionnaires using a Likert scale of 1-5. Analysis was conducted using multiple linear regression to determine the relationship between variables. The results of this study indicate that workload and job insecurity have a significant partial effect on the performance of employees in the Production Department at PT STL Indonesia (STL). The implication of these findings is that companies need to periodically evaluate work systems and task allocation to ensure workloads remain within optimal limits. Furthermore, to foster a sense of security at work, companies can maintain and improve open communication and information. Training programs can also be implemented to help employees better adapt to change.